The History of Popularization of Science in France - M. D. Romanova (Vestnik MGIMO-Universiteta, 2015)
The article discusses the process of popularization of science in France in terms of bilateral cooperation between scientists and the media. Mediator in the relationship of the two parties is a science journalist. The long history of interaction between researchers and journalists in France can serve as a theoretical model applicable to the Russian media system. Science journalist, acting primarily as a popularizer of science, is intended to bring to the uninitiated reader scientific facts in an accessible form. In this connection, still the question remains about the specialized education of science journalists: whether he should specialize in a particular field or possess the basics of writing and be able to transpose the complex scientific language. French popular science magazines are not only popular among scientists themselves who are willing to cooperate with publishers and participate in the preparation of the editions, but also among readers. Relations between science journalists and scientists should be considered at the theoretical and practical levels. The paper analyzes in detail the first level, which includes the history of the emergence of scientific journalism in France since the first edition of the scientificjournal in Europe, as well as peculiarities of the educational system in this field. A special role in shaping ideas about the role of science journalists belongs to the Association of Science Journalists of informational press, organization, which is actively involved in the development of trust between scientists and journalists.